Nasionalisasi Minyak dan Kudeta Iran 1953 - Putra, Rizki Adi; Hidayat, Wahyu (Program Studi Pendidikan Sejarah Fakultas Ilmu Sosial dan Hukum Universitas Negeri Jakarta, 2019)
The writing of the history of the Iranian Revolution in Indonesia has been overwhelming. But there is one story that is often forgotten in an effort to investigate the Iranian Revolution, namely the attempt to nationalize Iranian oil and the Iranian coup in 1953. Revolution is not a single incident that occurs suddenly, revolution is a series of processes after processes that can finally change the status quo. In Iran's efforts to nationalize its oil, it suffered strong opposition from the United Kingdom to mengigat Iranian oil is very important for Britain, especially for its navy. But the insistence on nationalization which finally raised Mossadeqh as Iran's prime minister, Mossadeqh supported nationalization as well as the Iranian people. To prevent Britain and America from carrying out a coup operation to overthrow Mossadeqh and restore Shah Reza Pahlevi to sit back in his power. After Shah Reza Pahlevi rose and Mossadeqh dropped, Iranian oil was dominated by America and Britain. Penulisan sejarah Revolusi Iran dalam Indonesia sudah banyak sekali. Tetapi ada satu kisah yang sering dilupakan dalam usaha menyelidiki Revolusi Iran yaitu upaya nasionalisasi minyak Iran dan kudeta Iran 1953. Revolusi bukanlah kejadian tunggal yang terjadi dengan tiba-tiba, revolusi merupakan rangkaian proses demi proses yang akhirnya dapat merubah keadaan status quo yang ada. Dalam upaya Iran untuk menasionalisai minyaknya mengalami pertentangan keras dari Inggris mengigat minyak Iran sangat penting untuk Inggris terutama untuk angkatan lautnya. Tetapi desakan untuk nasionalisasi yang akhirnya menaikan Mossadeqh sebagai perdana menteri Iran, Mossadeqh mendukung nasionalisasi begitu juga rakyat Iran. Untuk mencegahnya Inggris dan Amerika melakukan operasi kudeta untuk menjatuhkan Mossadeqh dan mengembalikan Shah Reza Pahlevi duduk kembali dikekuasaannya. Setelah Shah Reza Pahlevi naik dan Mossadeqh turun, minyak Iran dikuasai oleh Amerika dan Inggris.